Stress-induced nuclear speckle reorganization is linked to activation of immediate early gene splicing - Sung, Hsu-Min; Schott, Johanna; Boss, Philipp; Lehmann, Janina A.; Hardt, Marius Roland; Lindner, Doris; Messens, Joris; Bogeski, Ivan; Ohler, Uwe; Stoecklin, Georg (The journal of cell biology, 2023)
Current models posit that nuclear speckles (NSs) serve as reservoirs of splicing factors and facilitate posttranscriptional mRNA processing. Here, we discovered that ribotoxic stress induces a profound reorganization of NSs with enhanced recruitment of factors required for splice-site recognition, including the RNA-binding protein TIAR, U1 snRNP proteins and U2-associated factor 65, as well as serine 2 phosphorylated RNA polymerase II. NS reorganization relies on the stress-activated p38 mitogen-activated protein kinase (MAPK) pathway and coincides with splicing activation of both pre-existing and newly synthesized pre-mRNAs. In particular, ribotoxic stress causes targeted excision of retained introns from pre-mRNAs of immediate early genes (IEGs), whose transcription is induced during the stress response. Importantly, enhanced splicing of the IEGs ZFP36 and FOS is accompanied by relocalization of the corresponding nuclear mRNA foci to NSs. Our study reveals NSs as a dynamic compartment that is remodeled under stress conditions, whereby NSs appear to become sites of IEG transcription and efficient cotranscriptional splicing.
Gesehen am 02.09.2024